Pengaruh Promosi Jabatan dan Kompensasi terhadap Kinerja Karyawan yang Dimediasi Motivasi Kerja: (Studi pada Perusahaan RCI) - Sopani Siswantoro; Sutarmin Sutarmin (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2025)
This study aims to analyze the effect of compensation, work motivation, and promotion on employee performance at RCI. The study utilized a survey method, distributing a questionnaire via Google Form to collect data. A total of 100 respondents were selected through simple random sampling, ensuring that each employee had an equal chance of being included. The data was analyzed to determine both the partial and simultaneous effects of the variables under investigation. The results indicate that job promotion and compensation positively and significantly influence work motivation and employee performance. Additionally, work motivation was found to mediate the relationship between job promotion and compensation with employee performance. These findings emphasize that improving employee performance can be achieved when a company consistently offers fair compensation, transparent job promotion opportunities, and reinforces work motivation. Therefore, RCI can enhance its human resource potential through management policies that prioritize employee welfare and career development. This study offers practical insights for companies in developing strategies aimed at improving employee performance and provides academic contributions by exploring the relationship between compensation, job promotion, work motivation, and employee performance. Furthermore, it suggests that companies should foster an environment where employee motivation is a key focus to achieve sustainable organizational growth